2009
DOI: 10.1186/1471-2458-9-457
|View full text |Cite
|
Sign up to set email alerts
|

Income level and chronic ambulatory care sensitive conditions in adults: a multicity population-based study in Italy

Abstract: BackgroundA relationship between quality of primary health care and preventable hospitalizations has been described in the US, especially among the elderly. In Europe, there has been a recent increase in the evaluation of Ambulatory Care Sensitive Conditions (ACSC) as an indicator of health care quality, but evidence is still limited. The aim of this study was to determine whether income level is associated with higher hospitalization rates for ACSC in adults in a country with universal health care coverage.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 38 publications
4
70
2
6
Order By: Relevance
“…Kidney and urinary tract infections were the third most common cause of admissions. These findings are consistent with the findings described in the literature, which show that rates of admissions for ACSCs are higher among this age group 5,7,[49][50][51][52] . The most prevalent conditions among the 60 years and over age group were circulatory system diseases, the most common of which were heart failure, angina and cerebrovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kidney and urinary tract infections were the third most common cause of admissions. These findings are consistent with the findings described in the literature, which show that rates of admissions for ACSCs are higher among this age group 5,7,[49][50][51][52] . The most prevalent conditions among the 60 years and over age group were circulatory system diseases, the most common of which were heart failure, angina and cerebrovascular diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have reported varying rates of admissions for ACSCs across different countries. In Italy, Agabiti et al 7 observed rates of 26.1 per 10,000 population, while in Switzerland, Eggli et al 8 found rates of 10 per 1,000 population among patients with private health insurance. The most common causes of ACSC admissions described in the national and international literature are gastroenteritis, kidney and urinary tract infections, heart failure, angina, asthma, and diabetes mellitus [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Low income, however, remained associated even after multivariate analysis. A more recent study 21 showed an inverse gradient between income level and hospitalization rates for asthma and COPD. Other authors have also demonstrated the adverse effect of the worst income and education rates on respiratory diseases 5,22,23 , but they do not correlate these determinants with the outcome of hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, both these definitions identified COPD as an ambulatory care-sensitive condition. Previous studies showed that personal socioeconomic status, 23,29,30 health status, 24,31 and health care access 24,30,32 are associated with avoidable hospitalizations. To the best of our knowledge, however, few studies examined the relationship between COC and avoidable hospitalizations; the majority of these studies included several diseases, [33][34][35] but only 1 study focused on diabetes.…”
mentioning
confidence: 99%